(untitled) (Journal of Special Education and Rehabilitation, 2013)
For third time this year, the Open Access Week was organized, thus contributing to raising public awareness of open access in science. The event took place on 24th October at the hall for translation and interpretation at the Faculty of Philology in Skopje. Presenters at this event were: Dimitar Popovski, doctoral student at the Department of Information Science in Zagreb, Prof. Dr. Vladimir Trajkovski, Editor in Chief of Journal of Special Education and Rehabilitation (JSER) and Irina Shumadieva and Sead Dzigal, project coordinators of “Open Educational Resources initiatives in the Republic of Macedonia”. At the beginning, Dimitar Popovski stressed the purpose of this event which is promoting Open Access in the Republic of Macedonia and raising awareness of open access academic publishing. Open Access Week is, actually, a world-open access week and this event is happening in a total of 170-180 countries. In his speech, Dimitar Popovski emphasized the Macedonian Journal of Chemistry and Chemical Engineering as an online journal with the highest impact factor in Macedonia and continued with the presentation tools “Zotero” and “Mendeley” which represent online managers for organizing and sharing research resources. Prof. Dr. Vladimir Trajkovski addressed the attendees with the topic Open Journal System (OJS) of Philosophy which is a system for managing and publishing journals, developed by Public Knowledge Project (PKP). OJS is designed specifically to help researchers and faculties in the publication of peer-reviewed Open Access Journals. Further, Prof. d-r Trajkovski explain the purpose of the OJS, the need and the characteristics of the OJS, its flexibility and its advantages. At the end, there was a presentation by Irina Shumadieva and Sead Dzigal for Metamorphosis contribution in the field of open access and open educational resources, which highlighted that the developed tools and content are still used by stakeholders. A video streaming was provided for those who were not able to attend the event.